Shelley's poetry and prose : Authoritative texts, criticism - Shelley, Percy Bysshe; Reiman, Donald H.; Fraistat, Neil. (New York : Norton and company, 2007)
Annotated definitive texts of all of Shelley's greatest poetry as well as other poems frequently discussed and three prose works are combined with general critical studies of his art and thought and scholarly writings analyzing specific poems.
Includes bibliographical references (p. 775-783) and index.
Keywords: Shelley's poetry and prose; Shelley, Percy Bysshe